Implementation of Extreme Programing in the Stock Inventory Information - Pindriansyah; Ulfa, Maria; Amalia, Rahayu; Sobri, Muhammad; Komalasari, Dinny (Universitas Teknokrat Indonesia, 2025)
Inventory information system is a software designed and built to manage inventory effectively and in real-time. In addition, to support the acceleration of business growth, business people are required to be able to adapt to technological advances. Pins perfume shop is a shop that presents a wide variety of perfume collections with different fragrances. The process of managing inventory at the pins perfume shop is still carried out conventionally, which has several risks such as loss of documents, damage to documents, and errors in recording the amount of inventory. To minimize these risks and support the acceleration of business growth, the authors design and build a website-based inventory information system. The author uses the Extreme Programming (XP) method, this research was conducted at the pins perfume shop. With this digital platform, it helps make it easier for the pins perfume shop to manage inventory, and makes it easier to print inventory reports, which are useful in making the right business strategy decisions.